Epidemiological aspects of poisoning by arachnids in the Microregion of Furos de Breves, Marajó-Pará archipelago, Brazil (Research, Society and Development, 2021)
In Brazil, the high number of accidents with venomous animals is a serious public health problem. The study conducted an epidemiological analysis of arachnids poisoning in the micro-region of Furos de Breves, comprising the municipalities of Afuá, Anajás, Breves, Curralinho and São Sebastião da Boa Vista, Pará, Brazil, in the period from 2015 to 2017. epidemiological data were obtained from the Notifiable Diseases Information System, which are available on the Ministry of Health website. 123 cases of accidents involving arachnids were recorded, among which, poisoning by scorpions was predominant (83.7%). Most of the victims are from the municipality of Breves, male and brown. The frequency of accidents by scorpions was higher in April and June, while the months of February, April, July and October had high rates of araneism. The medical care time was carried out within 6 hours after the accident, and predominantly the cases evolved to cure without a record of deaths. These results can be explained mainly by human activities in this region that impact the habitats of these animals, and provide a chain of events that contribute to the increased risk of accidents with arachnids throughout the year.